KONSTRUKSI GARUK UNTUK KELESTARIAN SUMBERDAYA KERANG - Puspito, Gondo (Bumi Lestari, 2013)
Abstract Dredge is known as cockle collector which is not selective to the shell size and its operation damages the cockle’s resources. The objectives of this research were to obtain better dredge construction which was more productive and selective to the cockle size. The end of the teeth was bent 30o to increase number of the catch. Separator was used to make the dredge become more selective for the shell size. In this research, gap between separator grids was adjusted to economical size of cockle Anadara granosa, which was 40 mm long of shell. Results showed that dredge with 30o bended teeth caught 919 cockles, or 2.18 times more than standard teeth of dredge (412 cockles). The using of separator made dredge became more selective. It only retained cockle Anadara granosa and Anadara antiquata with length of shell l e” 39.96 mm and l e” 35.11 mm.
Keywords: Keywords: dredge, cockle collector, dredge teeth, separator